Inovação aberta no setor público: um panorama sistematizado de práticas e estratégias - Santos, Karen Thamilly Couto dos (Brasil, 2025)
This study aims to identify, synthesize and categorize open innovation practices and strategies implemented in the public sector, based on a systematic review of the academic literature. To this end, the PRISMA (2020) protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed. Data collection involved articles indexed in the Scopus, Web of Science and SciELO databases. After applying the eligibility criteria, 34 articles made up the corpus of analysis. The results cover two decades of research. The data was analyzed using the IRaMuTeQ software (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires), which made it possible to identify analysis classes based on the most recurrent and significant terms in the texts. The analysis resulted in six thematic classes, organized on the basis of semantic proximity, frequency and statistical relevance, representing key dimensions of open innovation in the public sector.